Identification of Fusarium solani f. sp. pisi (Fsp) Responsive Genes in Pisum sativum - Williamson-Benavides, Bruce A.; Sharpe, Richard M.; Nelson, Grant; Bodah, Eliane T.; Porter, Lyndon D.; Dhingra, Amit (Frontiers in Genetics, 2020)
Pisum sativum (pea) is rapidly emerging as an inexpensive and major contributor to the plant-derived protein market. Due to its nitrogen-fixation capability, short life cycle, and low water usage, pea is a useful cover-and-break crop that requires minimal external inputs. It is critical for sustainable agriculture and indispensable for future food security. Root rot in pea, caused by the fungal pathogen Fusarium solani f. sp. pisi (Fsp), can result in a 15-60% reduction in yield. It is urgent to understand the molecular basis of Fsp interaction in pea to develop root rot tolerant cultivars. A complementary genetics and gene expression approach was undertaken in this study to identify Fsp-responsive genes in four tolerant and four susceptible pea genotypes. Time course RNAseq was performed on both sets of genotypes after Fsp challenge. Analysis of the transcriptome data resulted in the identification of 42,905 differentially expressed contigs (DECs). Interestingly, the vast majority of DECs were overexpressed in the susceptible genotypes at all sampling time points, rather than in the tolerant genotypes. Gene expression and GO enrichment analyses revealed genes coding for receptor-mediated endocytosis, sugar transporters, salicylic acid synthesis and signaling, and cell death were overexpressed in the susceptible genotypes. In the tolerant genotypes, genes involved in exocytosis, and secretion by cell, the anthocyanin synthesis pathway, as well as the DRR230 gene, a pathogenesis-related (PR) gene, were overexpressed. The complementary genetic and RNAseq approach has yielded a set of potential genes that could be targeted for improved tolerance against root rot in P. sativum. Fsp challenge produced a futile transcriptomic response in the susceptible genotypes. This type of response is hypothesized to be related to the speed at which the pathogen infestation advances in the susceptible genotypes, and the preexisting level of disease-preparedness in the tolerant genotypes.